Common Ocular Diseases: Recent Observation from a Community Based Ophthalmological Clinic in Shaymoli, Dhaka (The Journal of Ad-din Women's Medical College, 2023)
Abstract not availableThe Journal of Ad-din Women's Medical College; Vol. 10 (1), Jan 2022; p 63-64